Calretinin Staining in Anorectal Line Biopsies Accurately Distinguished Hirschsprung Disease in a Retrospective Study. (November 2022) - Logan, Suzanna J.; Yin, Hong; Rogers, Beverly; Arva, Nicoleta; Conces, Miriam R.; Cope-Yokoyama, Sandy; Dehner, Louis P.; Galliani, Carlos; Garg, Shipra; He, Mai; Husain, Aliya N.; Keisling, Matthew; et al.
Introduction: The absence of submucosal ganglion cells does not reliably distinguish Hirschsprung disease from non Hirschsprung disease in anorectal line biopsies. Calretinin staining might be helpful in these biopsies. To determine its value, we analyzed calretinin positive mucosal neurites in anorectal line biopsies. Methods: Two pediatric pathologists, without access to patient data, evaluated calretinin positive mucosal neurites in anorectal line junctional mucosa in archival rectal biopsies contributed by 17 institutions. A separate investigator compiled patient information and sent data for statistical analysis. Results: Biopsies with anorectal junctional mucosa from 115 patients were evaluated for calretinin positive mucosal neurites. 20/20 Hirschsprung disease biopsies were negative. 87/88 non Hirschsprung disease biopsies and 7/7 post pullthrough Hirschsprung disease neorectal biopsies were positive. Statistical analysis of the 108 non pullthrough biopsies yielded an accuracy of 99.1% (sensitivity 100%, specificity 98.9%). Age range was preterm to 16 years. Biopsy size was less than 1 mm to over 1 cm. Conclusions: Absence of calretinin positive mucosal neurites at the anorectal line was highly accurate in distinguishing Hirschsprung disease from non Hirschsprung disease cases in this blinded retrospective study. Calretinin staining is useful for interpreting biopsies from the physiologic hypoganglionic zone up to the anorectal line.